2020
DOI: 10.9734/ajbgmb/2020/v5i430137
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Haematological Parameters in Plasmodium falciparum Infected Malaria Patients in an Urban Slum of Lagos, Nigeria

Abstract: The present study was carried to determine the changes in haematological parameters in P. falciparum infected patients in Ajeromi Ifelodun area of Lagos, Nigeria. Seventy (70) human subjects comprising of 50 P. falciparum malarial infected and 20 non-infected (control) subjects between 10-60 years were selected for this study. RDT test and microscopy were carried out to ascertain the presence of P. falciparum. They were grouped based on age criteria and level of parasitaemia. This work was carried out in the D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…The renal ischemia caused by the sequestration of the parasite into the microvasculature bed of the kidney could be the cause of high urea and creatinine in severe malaria. It was observed that serum protein decreased markedly in severe malaria infection, which is thought to be due to the influence of the parasite on protein synthesis ( Ozojiofor et al, 2020 ).…”
Section: Resultsmentioning
confidence: 99%
“…The renal ischemia caused by the sequestration of the parasite into the microvasculature bed of the kidney could be the cause of high urea and creatinine in severe malaria. It was observed that serum protein decreased markedly in severe malaria infection, which is thought to be due to the influence of the parasite on protein synthesis ( Ozojiofor et al, 2020 ).…”
Section: Resultsmentioning
confidence: 99%
“…In this study, a significant decrease in the haemoglobin (HGB) level was observed. Akogwu et al [37] reported decreased levels of PCV/HGB (anaemia) and Ozojiofor et al [16] also reported a decrease in the mean level of haematocrit (HCT/PCV), haemoglobin (HGB), red blood cells (RBC), and platelets (PLT) in P. falciparum infected patients compared to the healthy subjects. The decrease in HGB could be due to oxidative stress [38] and the breakdown of haemoglobin by the parasite in malaria infected patients and the subsequent removal of parasitized erythrocytes from circulation by the reticuloendothelial system.…”
Section: Discussionmentioning
confidence: 99%
“…Randomization was done by selecting patients with malaria after microscopic examination of thin and thick blood smears by the method of Cheesbrough [15] as reported by Ozojiofor et al, [16]. The number of parasites counted per 200 white blood cells was used to calculate parasite density on the basis of 8000 leukocytes per μl of blood for those slides that were positive.…”
Section: Parasitological Examinationmentioning
confidence: 99%